Workers Recruitment of PT. Perkebunan Nusantara XII Sirah Kencong Factory, Section of Kebun Bantaran - Aaqilah Rahmadhanti (International Research & Development for Human Beings (IRDH), 2024)
Black tea is one of the main products of PTPN XII Sirah Kencong. The black tea produced by this company is processed through CTC (cutting, tearing, and curling). In the process of making CTC black tea, workers is needed because the production process still requires a lot of human assistance. The purpose of this research is to find out how workers recruitment in PTPN XII Sirah Kencong is done. The research is using a qualitative method with data collection by observation, interview, and literature review. Workers’ recruitment in PTPN XII Sirah Kencong is carried out by the central division of this company if there is a position that will be vacant or in a certain period. The recruitment through internal sources is carried out by observing the careers of workers in the company, and the recruitment through external sources is carried out by holding open recruitment.